Antibiotic intravenous‐to‐oral switch guidelines: barriers to adherence and possible solutions. (27th January 2014) - Warburton, John; Hodson, Karen; James, Delyth
Abstract Objectives To identify reasons for poor adherence to antibiotic intravenous‐to‐oral switch guidelines and to explore the possible solutions. To rate the importance of the barriers and solutions identified, as perceived by a multidisciplinary expert panel. Methods Three‐round Delphi study in an expert panel comprising doctors, nurses and pharmacists, with concurrent semi‐structured interviews. Key findings The three rounds of the Delphi were completed by 13 out of the 30 healthcare professionals invited to participate. No nurses were included in the final round. Consensus was achieved for 28 out of 35 statements, with the most important barrier being that of inappropriate antibiotic review at the weekend, and the most important solution being to raise guideline awareness. The findings from the seven interviews (three doctors, two pharmacists and two nurses) complemented those from the Delphi study, although they provided more specific suggestions on how to improve the adherence to guidelines. Conclusion This study, using a combination of quantitative and qualitative methods, has identified several barriers to explore further and offered many practical solutions to improve practice. The importance of a multidisciplinary approach to address guideline non‐adherence was emphasised. Clinical guidelines must be well publicised and well written to prevent a feeling of guideline saturation in the healthcare populous. Novel approaches may have to be investigated in order to further encourage adherence with antibiotic intravenous‐to‐oral switch guidelines.